EDUCAS as an Intervention Program to Improve Stress ManagementSkills in Adolescents - Yunda Yuardani; Ribka Adelina Sinaga; Achmad Sabrani Fahmi; Putri Fauziah Wulandari; Eggi Monica Sihombing; Fazira Shinaia Rahmadhantya; Masithah (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Adolescents are a group that is vulnerable to stress, so education is needed to improve their ability to manage it. EDUCAS (Health Education for Stress Management in Adolescents) program was implemented at SMK Negeri 1 Tenggarong Seberang, Embalut Village, and was attended by 43 twelfth-grade students. Objective : This activity aimed to increase adolescents understanding of stress, including its definition, causes, and management strategies. Research Methods/ Implementation Methods : The method used was a pre-experimental design with a one group pre-test and post-test approach. The intervention was carried out through education on stress management and interactive quizzes. Results : Data analysis used the Wilcoxon Signed Rank Test to measure changes in knowledge before and after the intervention. The results showed an increase in the average score from 66.98 to 69.77. Total of 41.86% of participants experienced an increase in knowledge, 20.93% experienced no change, and 37.21% experienced a decrease. However, a p-value of 0.588 (>0.05) indicates that the increase was not statistically significant. Factors such as device limitations, short intervention duration, and shared device use are thought to have influenced the results. Conclusion/Lesson Learned : The enthusiasm of the participants and the increased awareness of the importance of stress management indicate the positive potential of the EDUCAS program. It is recommended that similar activities in the future be carried out with a longer duration, adequate facilities, and more interactive learning methods to achieve more optimal results.